PROMOTING A READING CULTURE AMONG UNIVERSITY STUDENTS - Shahobova Shahzoda Abdujamilovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
In recent years, the significance of reading in higher education has drawn increasing attention from educators, researchers, and policymakers. A well-developed reading culture among students contributes not only to academic success but also to personal and professional development. This paper explores the current state of reading habits among university students and identifies the factors that influence their reading behavior. Using a mixed-methods approach, including surveys and interviews, the study investigates both the challenges and opportunities in promoting a reading culture. The findings highlight the role of digital technologies, institutional support, peer influence, and individual motivation. The article concludes by recommending practical strategies that can be employed by educators and institutions to foster a sustainable and engaging reading environment.